Comparison of dexmedetomidine and dexamethasone as adjuvants to the ultrasound-guided interscalene nerve block in arthroscopic shoulder surgery: a systematic review and Bayesian network meta-analysis of randomized controlled trials - Wei, Xiu-Min; Liu, Zheng; Lv, Lian-Chao; Wu, Guang-Han; Sun, Peng-Yu; Gu, Chang-Ping; Shi, Peng-Cai (Frontiers in Medicine, 2023)
Abstract Introduction: Interscalene block (ISB) is widely regarded as the gold standard treatment for acute pain following arthroscopic shoulder surgery. However, a single injection of a local anesthetic for ISB may not offer sufficient analgesia. Various adjuvants have been demonstrated to prolong the analgesic duration of the block. Hence, this study aimed to assess the relative efficacy of dexamethasone and dexmedetomidine as adjuncts to prolong the analgesic duration for a single- shot ISB. Methods: The efficacy of adjuvants was compared using a network meta-analysis. The methodological quality of the included studies was evaluated using the Cochrane bias risk assessment tool. A comprehensive search of the PubMed, Cochrane, Web of Science, and Embase databases was conducted with a search deadline of March 1, 2023. Various adjuvant prevention randomized controlled trials have been conducted in patients undergoing interscalene brachial plexus block for shoulder arthroscopic surgery. Results: Twenty-five studies enrolling a total of 2,194 patients reported duration of analgesia. Combined dexmedetomidine and dexamethasone (MD = 22.13, 95% CI 16.67, 27.58), dexamethasone administered perineurally (MD = 9.94, 95% CI 7.71, 12.17), high-dose intravenous dexamethasone (MD = 7.47, 95% CI 4.41, 10.53), dexmedetomidine administered perineurally (MD = 6.82, 95% CI 3.43, 10.20), and low-dose intravenous dexamethasone (MD = 6.72, 95% CI 3.74, 9.70) provided significantly longer analgesic effects compared with the control group. Discussion: The combination of intravenous dexamethasone and dexmedetomidine provided the greatest effect in terms of prolonged analgesia, reduced opioid doses, and lower pain scores. Furthermore, peripheral dexamethasone in prolonging the analgesic duration and lowering opioid usage was better than the other adjuvants when used a single medication. All therapies significantly prolonged the analgesic duration and reduced the opioid dose of a single-shot ISB in shoulder arthroscopy compared with the placebo.